ANALYSIS OF CAPITAL STRUCTURE AND STICKY COST ON FINANCIAL PERFORMANCE IN FOOD AND BEVERAGE SUB-SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Nursamsi, Nursamsi; Mira, Mira; Firman Syah (CV. AFDIFAL MAJU BERKAH, 2024)
NURSAMSI. 2024. Analysis of Capital Structure and Sticky Costs on the Financial Performance of Companies Listed on the Indonesia Stock Exchange. Undergraduate Thesis. Department of Management, Faculty of Economics and Business, Muhammadiyah University Makassar. Main Supervised Mira and Co-Supervisor Firman Syah. The purpose of this research is a quantitative study aimed at analyzing the impact of capital structure and sticky costs on the financial performance of companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange. The sample for this study was drawn from the financial reports of companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange. The data used in this research is quantitative data obtained from the financial reports of companies from 2018 to 2022, sourced from the respective websites of food and beverage companies listed on the Indonesia Stock Exchange or from the website www.idx.co.id. This study employs secondary data. The research instruments used in this study include descriptive statistical analysis, panel data regression analysis, and hypothesis testing using F-test (Chiw Test) and Hausman Test. From the analysis of Debt To Equity Ratio (DER), it appears that companies may need to consider strategies to manage and reduce their dependence on debt in order to improve their financial structure and reduce long-term financial risks. Additionally, the analysis of Sticky Costs indicates that these costs are becoming increasingly unresponsive to fluctuations in production and sales volume. Furthermore, Return On Assets (ROA) is significant in optimizing financial performance over the study period, although improvement efforts are observed in the final year